Informal Education Pedagogy Transcendence from the 'Academy' to Society in the Current and Post COVID Environment - Ian David Jones; Geraldine Brady (MDPI AG, 2022)
The purpose of this paper is to consider the following two notions; (1) that the use of 'informal education pedagogies' within teaching and learning in the 'academy' can both support the learning process within the 'classroom' but also transcend to society via students; and (2) that synergies exist between informal education and social pedagogical concepts. The discussions are situated from the perspective of an experienced practitioner and academic who is currently teaching youth related degree courses within a Higher Education Institution. This experiential learning has informed knowledge acquisition, understanding and skills application from professional practice to the teaching environment. An experiential learning perspective will be the primary method adopted; the value of this paper lies in its potential to re-affirm that degree courses which embed a 'practice the practice' approach in their teaching methodology support the embedding of core values of the said discipline. The paper argues that the ethically value-based principles and practice of informal education pedagogy, and social pedagogy, are relevant for the current and post COVID-19 pandemic environment.